Shoak quwaid e urdu (urdu grammar wa insha pardazi) - Muhammad masood ul haq (Shoak puublisher Pakistan)
"Shouk Qawaid-e-Urdu (Urdu Grammar wa Insha Pardazi)" is a comprehensive guide to mastering Urdu grammar and creative writing, offering clear explanations and practical exercises to enhance language skills.